Deauthorization of the Religious Leader Role in Countering Covid-19: Perceptions and Responses of Muslim Societies on the Ulama’s Policies in Indonesia - Faisal (2022)
Ulama as epicenters of religious leader in spreading religious teachings in Muslim societies have experienced deauthorization. This study aims to reflect the Muslim societies’ perceptions and responses on the Ulama policies in countering Covid-19 in Indonesia. This study uses observation, interviews, and literature review as data sources. This study presents a theoretical perspective on the deauthorization of the Ulama role in Indonesia in handling Covid-19. This study found three socioreligious aspects. Firstly, less public’s knowledge and understanding of Covid-19 socialization confirms multiple interpretations at the grass road level. Secondly, the socialization of the Ulama policies has not been carried out effectively, as seen in several cases, such as the rejection of the mosque closure and the prohibition of other religious activities, due to the lack of public knowledge about this epidemic. Thirdly, government policies on Large-Scale Social Restrictions (PSBB) which are totally supported by the MUI (Indonesian Ulama Council) as the representation of Indonesian Muslim scholar have not been able to suppress the Muslim societies’ enthusiasm in the practice of religious activities. It indeed demonstrates Ulama’s deauthorization in countering Covid-19 pandemic for Muslim societies in Indonesia